Alactic base excess is not a sensitive or specific diagnostic tool for outcome in horses with colic - Corinne E. Crosby; Annette O’Connor; Amelia S. Munsterman (Frontiers in Veterinary Science)
IntroductionColic is a significant source of morbidity and mortality in horses, and no single biomarker can distinguish surgical from medical colic or predict mortality. Alactic base excess (ABE) has shown an association with mortality and renal insufficiency in humans but has not been evaluated in veterinary species. The purpose of this study was to determine the value of ABE as a diagnostic tool for horses treated for gastrointestinal disease.MethodsThis retrospective case series evaluated horses admitted for acute gastrointestinal disease over a 5-year period (2019–2024). Signalment, physical examination findings, venous blood gas analysis results, packed cell volume and total solids on admission, findings in cases undergoing exploratory celiotomy, and outcome were collected from the medical record. Variables were evaluated individually, and by multivariate analysis for sensitivity and specificity to differentiate medical from surgical colic, strangulating versus non-strangulating lesions, and between survivors and non-survivors after surgical intervention. Optimal Youden cut-off values and area under the receiver operating curve (AUC) were calculated.ResultsFive hundred and thirty eight horses met the inclusion criteria. Multiple presentations by the same horse were each counted as individual presentations, resulting in 585 admissions. While ABE was higher in surgical cases that did not survive (p = 0.029), it did not discriminate between medical and surgical colic or between survivors and non-survivors as a sole diagnostic or multivariate modality. The best predictor of medical or surgical treatment was serum glucose levels (AUC = 0.76, Se = 0.76, Sp = 0.67). Serum glucose levels were also the best predictor of strangulating versus non-strangulating lesions (AUC = 0.81, Se = 0.67, Sp = 0.83). The model for survival after surgery included age and serum L-lactate (AUC = 0.76, Se = 0.73, Sp = 0.69).DiscussionElevations in alactic base excess values in surgical cases that did not survive may indicate compensation for hyperlactatemia with complex metabolic derangements. Our investigation supports the use of hyperglycemia and hyperlactatemia as markers of severity for horses with gastrointestinal disease.